PERKEMBANGAN MUTAKHIR PENDIDIKAN BAHASA INDONESIA: KURIKULUM 2013 SEKOLAH DASAR - Wulan, Neneng Sri (Mimbar Sekolah Dasar, 2014)
Despite changes intended to improve educational curriculum to better direction but in the process of implementation still experiencing problems. Many things that cause it. One is the lack of understanding of the particulars of the curriculum in 2013 particularly for learning Indonesian language and literature. There are still many elementary school teachers who have not mastered, even understand it. Based on observations made in Banten province, nearly 50% of primary school teachers do not understand the particulars of learning Indonesian language and literature in the curriculum in 2013. It is certainly very unfortunate, because the teacher is one of the cornerstones of educational success. If teachers do not understand and master the curriculum to be applied in the classroom, of course it will have an impact on student learning outcomes. Therefore the discussion of learning Indonesian language and literature for primary school based curriculum in 2013 is certainly very important and necessary for practitioners, especially those that work in the world of elementary school. Discussion about learning Indonesian language and literature based curriculum in 2013 is expected to be one of the doors to open insight, understanding, and mastery, which will have an impact on learning outcomes over the maximum. Keywords: learning Indonesian language and literature, elementary school, curriculum 2013.